Stres Kerja Dengan Kinerja Islam Rumah Sakit Aisyiyah - Achmad Zaini; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research was aimed to find out the effect of work stress against the Islamicperformance of nursing employees part Aisyiah Bojonegoro hospital. This research used questionmaires in primary data collection and quantitative approaches.Experiments were done using simple linear regression, where the dependent variable (Y) is islamic performance and the independent variable (X) is job stress. The research sample was taken by probability sampling with simple random sampling method. The research sample was 56 employees of Aisyiah Bojonegoro hospital.Based on the findings, it obtained simple linear regression equation: Y = 5,737 + (-0,640 X). The results of this research showed that the influence of job stress has positive effect and signifficant against the Islamic performance of nursing employees Aisyiah Bojonegoro hospital. The R2 on this research showed the number 0.473, which mean that 47.3% of islamic performance can be explained by the variables of job stress.